Burdened By Race Coloured Identities in Southern Africa - Adhikari, Mohamed (UCT Press, 2009)
Since its emergence in the late 19th century, coloured identity has been pivotal to racial thinking in southern Africa. The nature of colouredness is a highly emotive and controversial issue as it embodies many of the racial antagonisms, ambiguities and derogations prevalent in the subcontinent. Throughout their existence coloured communities have had to contend with being marginal minorities stigmatised as the insalubrious by-products of miscegenation. Burdened By Race showcases recent innovative research and writing on coloured identity in southern Africa. Drawing on a wide range of disciplines and applying fresh theoretical insights, the book brings new levels of understanding to processes of coloured self-identification. It examines diverse manifestations of colouredness, using interlinking themes and case studies from South Africa, Zimbabwe, Zambia and Malawi to present analyses that challenge and overturn much of the conventional wisdom around identity in the current literature.